Alterations of the Temporomandibular Joint on Magnetic Resonance Imaging according to Growth and Development in Schoolchildren. (19th December 2012) - Tanaka, Tatsurou; Konoo, Tetsuro; Habu, Manabu; Oda, Masafumi; Kito, Shinji; Kodama, Masaaki; Kokuryo, Shinya; Wakasugi-Sato, Nao; Matsumoto-Takeda, Shinobu; Nishida, Ikuko; Morikawa, Kazumasa; Saeki, Katsura; et al.
Abstract : The paper explains the alterations of the temporomandibular joint (TMJ) visualized by magnetic resonance imaging (MRI) according to the growth and development of schoolchildren. Appearance and disappearance of a "double contour-like structure" (DCLS) of the mandibular condyle on MRI according to the growth and development of schoolchildren were demonstrated. In addition, possible constituents of DCLS and the significance of detection of DCLS on MRI were also speculated. The relationship between red marrow and yellow marrow in the articular eminence of temporal bone, the disappearance of DCLS, and alterations of the mandibular condyle have been elucidated.